Behavioural intervention practices for stereotypic and repetitive behaviour in individuals with autism spectrum disorder: a systematic review - PATTERSON, STEPHANIE Y; SMITH, VERONICA; JELEN, MICHAELA (Developmental medicine and child neurology, 2010)
Aim  The purpose of this systematic review was to examine the quality of conduct of experimental studies contributing to our empirical understanding of function‐based behavioural interventions for stereotypic and repetitive behaviours (SRBs) in individuals with autism spectrum disorders (ASDs). Method  Systematic review methodology was used to identify relevant articles, to rate the level of evidence and quality of conduct of the studies, and to extract data systematically. Results  Ten single case studies examining 17 participants (14 males, 3 females; age 2y 11mo–26y) diagnosed with various ASDs were included. Overall, studies reported decreases in SRBs using behavioural interventions and some collateral increase in desirable behaviours. Interpretation  Only a small number of intervention studies for SRBs explicitly state the function of the behaviour; therefore, relatively little is known about the efficacy of SRB interventions in relation to the range of possible behavioural functions. Evidence supporting SRB interventions is preliminary in nature, and caution should be used in choosing and implementing SRB intervention practices for individuals with ASDs.